2018
DOI: 10.1242/bio.031807
|View full text |Cite
|
Sign up to set email alerts
|

Niclosamide rescues microcephaly in a humanized in vivo model of Zika infection using human induced neural stem cells

Abstract: Zika virus (ZIKV) is a mosquito-transmitted flavivirus with a causative link to microcephaly, a condition resulting in reduced cranial size and brain abnormalities. Despite recent progress, there is a current lack of in vivo models that permit the study of systemic virus on human neurons in a developing organism that replicates the pathophysiology of human disease. Furthermore, no treatment to date has been reported to reduce ZIKV-induced microcephaly. We tested the effects of ZIKV on human induced neural stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…For example, novel anti-ZIKV activities of enoxacin, amodiaquine and niclosamide were discovered recently using human neural progenitor cells, human pluripotent stem cell-derived cortical neural progenitor cells, and human induced neural stem cells, respectively (Cairns et al, 2018;Xu et al, 2019;Zhou et al, 2017).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, novel anti-ZIKV activities of enoxacin, amodiaquine and niclosamide were discovered recently using human neural progenitor cells, human pluripotent stem cell-derived cortical neural progenitor cells, and human induced neural stem cells, respectively (Cairns et al, 2018;Xu et al, 2019;Zhou et al, 2017).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Amodiaquine is an anti-malaria drug, which also possesses antiviral activities against DENV, HCV, RRV, SINV, WNV, EFV, EBOV, LASV, RABV, VZV, and HSV-1 in immortalized cell cultures (Boonyasuppayakorn et al, 2014;Hulseberg et al, 2019;Mazzon et al, 2019). Niclosamide is an orally bioavailable anthelmintic drug, which inhibits the broadest range of viruses in vitro and, in some cases, in vivo (Cairns et al, 2018;Fang et al, 2013;Huang et al, 2017;Hulseberg et al, 2019;Jurgeit et al, 2012;Kao et al, 2018;Mazzon et al, 2019;Stachulski et al, 2011;Wang et al, 2016;Wu et al, 2004). These safe-in-man BSAAs represent promising drug candidates.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Niclosamide, a category B antihelmintic drug approved by FDA, was capable to inhibit ZIKV infection and although its antiflaviviral effect has been associated to its ability to neutralize endolysosomal pH and interfere with pH-dependent membrane fusion, in the case of ZIKV it seems that it was affecting other postentry steps [80]. In addition, recently, it has been reported that niclosamide decreases ZIKV production, partially restores differentiation, and prevents apoptosis in human induced NSCs; even more, it can partially rescue ZIKV-induced microcephaly and attenuate infection in a developed humanized ZIKV-infected embryo model in vivo [81]. Likewise, tenovin-1, which represses cell growth and induces apoptosis in cells expressing p53 by inhibiting the protein-deacetylating activities of SirT1 and SirT2 and, thus, affects endosome functions, potently inhibits ZIKV infection in primary placental fibroblast cells [63].…”
Section: Endosomal Fusionmentioning
confidence: 99%
“…Niclosamide is an orally bioavailable anthelmintic drug and potential antineoplastic agent. In addition, it inhibits the broadest range of viruses, including HSV-2, in vitro and, in some cases, in vivo [28][29][30][31][32][33][34][35][36][37]. It was shown that niclosamide induces endosomal neutralization and prevents virus entry into host cells.…”
Section: Discussionmentioning
confidence: 99%